Perancangan Motif Batik Sumber Ide Bangau Bluwok Melalui Teknik Batik Tulis - Sandra Glodia; Sarah Rum Handayani (Hastagina : Jurnal Kriya Seni, 2023)
This design was made as a form of developing batik motifs with the source of the idea of bluwok cranes. This isagainst the background of the phenomenon of decreasing the population of bluwok herons, so wants to show the beautyof the bird which is now rarely found in batik motifs. In addition, cranes have philosophical values that can be developedinto the basis for designing the basic structure of batik patterns. The method used in this design is the method of creatingworks SP. Gustami, through three main stages, namely the exploration, design, and embodiment stages. The techniqueused in this design is in the form of a writing batik technique with the bidding of the colet technique using a remasol dye.The result of this design is in the form of written batik products as textile materials for women's clothing aged 20-25. Theresulting motifs lead to contemporary batik motifs that tend to be free and not bound by certain rules. The visuals of thedashing crane are processed into motifs that tend to be weakly started like women (feminine), so that they have a noveltyvalue. The technique used in this design is batik writing with the coloring of the colet technique using remasol dyes.